Comparison of short-term oncologic outcomes in open, laparoscopic and robotic radical gastrectomy for the treatment of gastric cancer - Sibel Yaman; Zafer Teke; Sercan Yüksel; Ugur Topal; Hüseyin Karatay; Hürü Ceren Gökduman; Erdal Karaköse; Hasan Bektaş (Journal of Minimal Access Surgery)
Aim: Surgical resection remains the cornerstone treatment for gastric cancer, which ranks as the fifth most common cancer globally. Although minimally invasive surgical techniques are gaining popularity, their safety and oncological adequacy remain subjects of ongoing debate. This study aims to contribute to the medical literature by comparing open, laparoscopic and robotic gastrectomy techniques in the treatment of gastric cancer, focusing on short-term oncological outcomes. Materials and Methods: Patients aged 18 years and older who underwent surgery for gastric adenocarcinoma at our institution between April 2020 and September 2022 were included in the study. The patients were categorised into three groups based on the surgical approach: open gastrectomy, laparoscopic gastrectomy and robotic gastrectomy. Demographic data, intraoperative and post-operative findings, tumour characteristics and short-term morbidity and mortality outcomes were analysed retrospectively. Results: A total of 109 patients (37 females [33.9%] and 72 males [66.1%]) with a mean age of 63.1 ± 11.4 years were included. The operative time was significantly shorter in the open gastrectomy group compared to the laparoscopic and robotic groups (P = 0.012). The initiation of oral intake and post-operative hospital stay were significantly shorter in the robotic gastrectomy group (P < 0.001). At 1-year follow-up, disease-free survival rates were higher, and mortality rates were lower in the robotic gastrectomy group compared to the other groups (P = 0.030). Furthermore, the completion rate of adjuvant therapy was significantly higher in the robotic group than in the other groups (P = 0.008). Conclusion: In conclusion, minimally invasive surgical techniques, particularly robotic gastrectomy, provide a safe and oncologically adequate alternative to open surgery for the treatment of gastric cancer. These methods can be safely employed in selected patients by experienced teams at high-volume centres.